PERENCANAAN ARSITEKTUR VISI DI RUMAH SAKIT TNI AU SOEMITRO MENGGUNAKAN PENDEKATAN TOGAF ADM 9.2 - Birgita Yolanda Hermawan; Riza Akhsani Prayoga; Raulia Riski (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
The development of information technology (IT) has brought significant changes in various industries, including the health sector. This research focuses on architectural business planning at the Soemitro Air Force Hospital using the TOGAF ADM 9.2 approach. Even though this hospital has implemented an Electronic Medical Record (E-MR) system, various problems such as poor integration, data duplication, and input errors still hamper operational performance. The aim of this research is to develop a comprehensive architectural business to improve operational efficiency and quality of hospital services. This study begins with an evaluation of the hospital's business and strategic needs, followed by careful planning in accordance with the IS/IT strategy. The use of the TOGAF ADM framework was chosen because of its flexibility and opensource nature, which facilitates the development of an optimal organizational architecture. It is hoped that the research results will provide guidance for hospitals in integrating information technology with their business processes, increasing productivity and improving the quality of health services. Thus, this research not only contributes to information technology management in the health sector but also enriches understanding of the effective and efficient implementation of architecture vision in the hospital context. Implementing a proper IS/IT strategy is expected to align hospital IT needs with business process demands, reduce errors and data duplication, and increase patient satisfaction. This research underlines the importance of strategic planning in information vision development to achieve long-term organizational success.